Intelligent document‐filling system on mobile devices by document classification and electronization. (28th January 2020) - Lu, Jing; Wu, Shihong; Xiang, Zhiyu; Cheng, Hanlei
Abstract: Both of an automatic classification method for original documents based on image feature and a layout analysis method based on rule hypothesis tree are proposed. Then an intelligent document‐filling system by electronizing the original documents, which can be applied to cellphones and pads is designed. When users are filling documents online, information can be automatically input to the financial information system merely by taking photos of the original documents. By this means can not only save time but also ensure the accuracy between the data online and that on the original documents. Experiments show that the accuracy of document classification is 88.38%, the accuracy of document‐filling is 87.22%, and it takes 5.042 seconds dealing with per document. The system can be applied to financial, government, libraries, electric power, enterprises and many other industries, which has high economic and application value.